Triostin A Derived Cyclopeptide as Architectural Template for the Alignment of Four Recognition Units** - Kotyrba, Ursula M (ChemistryOpen, 2014)
The DNA bisintercalator triostin A is structurally based on a disulfide-bridged depsipeptide scaffold that provides preorganization of two quinoxaline units in 10.5 Å distance. Triostin A analogues are synthesized with nucleobase recognition units replacing the quinoxalines and containing two additional recognition units in between. Thus, four nucleobase recognition units are organized on a rigid template, well suited for DNA double strand interactions. The new tetra-nucleobase binders are synthesized as aza-TANDEM derivatives lacking the N-methylation of triostin A and based on a cyclopeptide backbone. Synthesis of two tetra-nucleobase aza-TANDEM derivatives is established, DNA interaction analyzed by microscale thermophoresis, cytotoxic activity studied and a nucleobase sequence dependent self-aggregation investigated by mass spectrometry.